EVALUATION OF NI-IN-NI MULTILAYERS FOR THERMALLY STABLE OHMIC CONTACTS TO N-GAAS - HSIA, ST; LEE, CP; HWANG, HL (My University, 1995)
A thermally stable, low resistance ohmic contact system Ni-Ln-Ni to n-GaAs was investigated. The lowest value of the specific contact resistance rho(c) was 1.71 x 10(-4) Omega cm(2). Hearing the contact up to 400 degrees C for 5 h did not obviously change the value of rho(c). It was observed by Auger electron spectroscopy and X-ray diffraction that Ni-Ln compounds, Ga-Ni and InAs formed at the metal-GaAs interface. It was noted that In reacted with GaAs and formed a heterojunction ohmic contact (such as InAs-InxGa1-xAs-GaAs) and due to the low melting point (156 degrees C) of In, additions of Ni are needed to completely react the remaining In to form a high melting point compound.
Keywords: AUGER ELECTRON SPECTROSCOPY; GALLIUM ARSENIDE; CONTACT RESISTANCE; NICKEL